Analisis Kebijakan Penggunaan Tenaga Kerja Asing Di Indonesia (Dampak Dikeluarkannya Peraturan Presiden (Perpres) Nomor 20 Tahun 2018 Tentang Penggunaan Tenaga Kerja Asing) - Yitawati, Krista (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2018)
The consequences of globalization and liberalization of trade and investment, have an impact on the number of Foreign Workers (TKA) working in Indonesia and to support the national economy and the expansion of employment opportunities through increased investment, the government issued Presidential Regulation (Perpres) Number 20 of 2018 concerning the Use of Labor Foreign. For this reason, this study aims to analyze the policy of using foreign workers in Indonesia as a result of the issuance of Presidential Regulation (Perpres) Number 20 of 2018 concerning the Use of Foreign Workers. The research method that I use is normative juridical. The results of this study, namely the use of foreign workers in Indonesia currently supported by the issuance of Presidential Regulation (Perpres) Number 20 of 2018 concerning the Use of Foreign Workers (TKA), will have a good impact on the development of investment from abroad to Indonesia. Because basically this Presidential Regulation aims to simplify the procedure for using foreign workers to increase investment, not to facilitate the requirements of foreign workers entering Indonesia. The more investors or investors investing in Indonesia, the more new jobs that can be opened.